Advances in Molecular Mechanisms for Traditional Chinese Medicine Actions in Regulating Tumor Immune Responses - Huang, Han; Fang, Jiansong; Fan, Xiude; Miyata, Tatsunori; Hu, Xiaoyue; Zhang, Lihe; Zhang, Liangren; Cui, Yimin; Liu, Zhenming; Wu, Xiaoqin (Frontiers in Pharmacology, 2020)
Traditional Chinese medicine (TCM) has been used in China and other Asian countries for thousands of years because of its anti-inflammatory and anti-cancer activity. The interest in TCM is rising due to its synergistic effect on tumor cells and tumor immunosuppressive microenvironment (TIM). Conventional treatments for cancer usually focus on one specifical target, ignoring the interaction between tumor cells and TIM. It is often difficult to achieve the therapeutic effect as expected, while TCM has many biologically active ingredients, this characteristic of TCM fits well with the whole system and multi-target cancer treatment. Therefore, here we summarize the effect and molecular mechanisms of TCM on regulating TIM via remolding immunosuppressive cells (e.g., restoring dendritic cells antigen presentation function, enhancing NK cells-mediated killing activity, restraining myeloid derived suppressor cells funtion), inhibiting angiogenesis and lymphangiogenesis，as well as regulating cancer cells via inhibiting proliferation, invasion and metastasis and enhancing antitumor immune responses (e.g., promoting class MHC molecules expression and inhibiting PD-1/PD-L1 signaling). In addition, we discuss the advantages and disadvantages of TCM on cancer treatment as well as current therapeutic challenges and strategies. Hope it can be helpful for clinical potential of TCM in cancer prevention and treatment.